Influence of storage temperature on vickers microhardness of resin composite - Mayyadah Alomozainy (Journal of Dentomaxillofacial Science, 2018)
Objective: The purpose of this study is to evaluate the effect of three storage temperatures on microhardness of high- and low-viscosity bulk-fill materials and compare them with conventional resin-based composite materials.Material and Methods: Six composite resin-based materials were used in this study (TN, TNB, TNF, FZ250, FB, and FBF), samples were subdivided into three groups based on the pre-curing storage temperature (5°C, 23°C, 37°C). Light polymerization for each material was performed based on the manufacturer’s recommendation using a Bluephase G2 curing unit (Ivoclar Vivadent, Schaan, Liechtenstein) in a high-intensity mode with an irradiance of 1200 mW/cm2. Vickers hardness values of the top and the bottom surfaces of each sample were evaluated using a NOVA 130series, Vickers and Knoop hardness testing instrument under a 200-gram load and a dwell time of 10 seconds.Results: When the tested materials were stored at room temperature (23°C) before testing in the present study, they failed to reach the minimum 80% of the mean bottom to top hardness value ratio except for FZ250 and FBF, where they reached 97.8% and 83.2% respectively.Conclusion: Despite the promising results from this preliminary study, regarding improvement of microhardness with refrigerated composite resins, further research has to be conducted. The enhancement of hardness values associated with preheated composites could be beneficial in countries with warm climates, such as Saudi Arabia.